Cuphea vazquezii (Lythraceae), a yellow-flowered new species from the Cerro Grande, Sierra de Manantlán, Colima, Mexico - Padilla-Lepe, Jesús (Phytotaxa, 2024)
Cuphea vazquezii (subgen. Cuphea, sect. Archocuphea, Lythraceae), a minute new species from Cerro Grande, Comala, Colima, Mexico, is described and illustrated. It is morphologically similar to C. mimuloides, from which it differs in having a none-rhizomatous habit; mostly alternate leaves and flowers; larger leaf blades; shorter pedicels; spurred floral tubes; two yellow petals; deflexed nectariferous disc; and larger seeds. According to IUCN criteria, the species was assessed as critically endangered (CR).